Reverse and Forward Electron Flow-Induced H2O2 Formation Is Decreased in α-Ketoglutarate Dehydrogenase (α-KGDH) Subunit (E2 or E3) Heterozygote Knock Out Animals - Gergő Horváth; Gergely Sváb; Tímea Komlódi; Dora Ravasz; Gergely Kacsó; Judit Doczi; Christos Chinopoulos; Attila Ambrus; László Tretter (MDPI AG, 2022)
α-ketoglutarate dehydrogenase complex (KGDHc), or 2-oxoglutarate dehydrogenase complex (OGDHc) is a rate-limiting enzyme in the tricarboxylic acid cycle, that has been identified in neurodegenerative diseases such as in Alzheimer's disease. The aim of the present study was to establish the role of the KGDHc and its subunits in the bioenergetics and reactive oxygen species (ROS) homeostasis of brain mitochondria. To study the bioenergetic profile of KGDHc, genetically modified mouse strains were used having a heterozygous knock out (KO) either in the dihydrolipoyl succinyltransferase (DLST+/−) or in the dihydrolipoyl dehydrogenase (DLD+/−) subunit. Mitochondrial oxygen consumption, hydrogen peroxide (H2O2) production, and expression of antioxidant enzymes were measured in isolated mouse brain mitochondria. Here, we demonstrate that the ADP-stimulated respiration of mitochondria was partially arrested in the transgenic animals when utilizing α-ketoglutarate (α-KG or 2-OG) as a fuel substrate. Succinate and α-glycerophosphate (α-GP), however, did not show this effect. The H2O2 production in mitochondria energized with α-KG was decreased after inhibiting the adenine nucleotide translocase and Complex I (CI) in the transgenic strains compared to the controls. Similarly, the reverse electron transfer (RET)-evoked H2O2 formation supported by succinate or α-GP were inhibited in mitochondria isolated from the transgenic animals. The decrease of RET-evoked ROS production by DLST+/− or DLD+/− KO-s puts the emphasis of the KGDHc in the pathomechanism of ischemia-reperfusion evoked oxidative stress. Supporting this notion, expression of the antioxidant enzyme glutathione peroxidase was also decreased in the KGDHc transgenic animals suggesting the attenuation of ROS-producing characteristics of KGDHc. These findings confirm the contribution of the KGDHc to the mitochondrial ROS production and in the pathomechanism of ischemia-reperfusion injury.